Guanidino compounds with native GABA(A) δ receptor selectivity: a tale of homeostatic compensation in δ-KO mice - Meera, Pratap; Uusi-Oukari, Mikko; Wallner, Martin; Lipshutz, Gerald S. (Springer Science and Business Media LLC, 2026)
Altered GABAergic transmission has been implicated in the neurological symptoms of metabolic disorders associated with guanidino compound (GC) accumulation. Building on previous findings that selected GCs act as direct orthosteric GABAA​ receptor (GABAR) agonists, we now asked whether these GCs act preferentially on high-affinity extrasynaptic δ subunit-containing receptors (δ-GABAs). Using whole-cell patch clamp recordings from mouse cerebellar granule cells (CGCs) in brain slices of wild-type and δ-subunit knockout (δ-KO) mice, together with 5 nM [³H]muscimol displacement assays on WT and δ-KO forebrains, we compared the actions of four structurally GABA-like GCs — guanidinoacetate (GAA), β-guanidinopropionate (β-GPA), guanidinoethanesulfonate (GES), and γ-guanidinobutyrate (γ-GBA). These compounds activated CGC GABARs in cumulative concentration-response curves and displaced the highly δ-GABAR-selective ligand [3H]muscimol suggesting δ-GABAR-selective orthosteric agonist actions. In δ-KO forebrains, total [³H]muscimol binding was reduced by ~ 50%, confirming the loss high-agonist-affinity but low-abundance (~ 5% of total forebrain GABARs) δ-GABARs. δ-KO CGCs showed markedly reduced agonist sensitivity, with EC₅₀ values (µM, WT/δ-KO): GABA (2/6) < β-GPA (3/8) < GAA (4/14) < GES (32/72) < γ-GBA (44/219). The modest loss of agonist sensitivity for GABA and the four GABA-mimetic GCs in δ-KO CGCs is consistent with compensatory upregulation of non-δ extrasynaptic GABARs containing only α and β subunits, as previously described (Tretter et al., JBC 2001), explaining the preserved tonic inhibition in δ-KO neurons. Our findings demonstrate that GABA-mimetic GCs preferentially target δ-GABARs and suggest that homeostatic compensation by αβ-type GABARs is a key adaptive mechanism maintaining inhibitory tone in δ-KO CGC neurons.